Assai and the transmission of Chagas disease: a review (Research, Society and Development, 2022)
Chagas disease consists of a systemic infection of essentially chronic evolution caused by the flagellate protozoan Trypanosoma cruzi, which has as its vector the beetle of the triatome genus known as kissing bug. In Brazil, epidemiological data show high numbers of oral transmission, mainly in the Northern region. In the state of Pará, diagnosed cases of oral infection are mostly related to the consumption of assai (Euterpe oleracea), and are on the rise, which reinforces the need for surveillance and control strategies against the aggravation of the disease. This research aimed to organize data through a bibliographical review referring to Chagas disease infection transmitted by the consumption of assai in the city of Belém, Pará, in the last 10 years. The researched articles were categorical in relating the consumption of assai to the transmission of Chagas disease in the Amazon region, especially in the city of Belém/PA, either by confirming cases through outbreaks or diagnostic experiments of T. cruzi in assai samples. Cases are presented through sporadic outbreaks, however there is suspicion of widespread underreporting. Different authors converged on the fact that it is necessary to qualify the agents involved in the assai production chain, in order to reduce contagion through this food. The main solution seems to lie in educating both consumers and producers.